(untitled) (Bangladesh Medical Journal Khulna, 2021)
Background: Tibolone is a synthetic hormone relplacemert therpy prepration with estrogenic, progestogenic and androgenic tissue selective mechanism of action. It has advantages over traditional preparations of estrogen and progesterone considering the risks and adverse effects. Objective: To evaluate the extent of effectiveness and adverse effects of Tibolone. Method: This clinical trial was done in Khulna Medical College Hospital between January to December 2019. Postmenopusal women were selected by inclusion and exclusion criteria. Alternate participant was included in two different group. Participants of group A was treated with Tibolone for 6 months and participants of group B was treated with placebo for 6 months. Each participant was followed up after 3 and 6 months. Four categories of postmenopausal symptoms (hot flushes, night sweats, sleep disturbance and mood swinging) were evaluated. Participants were monitored for any adverse effects. Severity of postmenopausal symptoms was measured by using menopausal visual analogue scale. Results: Total 90 partcipants, were enrolled in this study, half of them were included in each group. Baseline assessment in group A participants revealed mild, moderate and severe symptoms in 05 (12%), 29 (64%) and 11 (24%) women respectively. After 6 months of treatment with tibolone, 35 (78%) participants became asymptomatic. This improvement is statistically significant (p<0.001). In group B, participant’s baseline assessment revealed mild, moderate and severe symptoms in 07 (16%), 28 (62%) and 10 (22%) cases respectively. After 6 months of treatment with placebo, 02 (05%) women were asymptomatic. This improvement is not statistically significant. No adverse event was observed during treatment with tibolone. Comparison between the tibolone and placebo treatment group showed, tibolone treatment is better. Conclusion: Tibolone effectively relieves the postmenopausal symptoms and improves the quality of women’s health at menopause. Bang Med J Khulna 2020: 53 : 31-34